Effect of latitude and sky clearance factor on the effectiveness of solar tracking strategies. Issue 1 (1st January 2019) - Al-Rawahi, N. Z.; Al-Azri, N. Z.
Abstract: Solar energy is gaining more grounds in the power generation industry. The effectiveness of solar tracking systems depends on the location's latitude. In addition, sky clearance has an effect on the received solar radiation. Therefore, it is important to know the effect of both factors in order to select the most appropriate system for each location. While there are many studies concentrated on either of these effects, there are no studies for their joint effect. Here, the combined effect of latitude and sky clearance on the performance of solar tracking systems is presented using data from seven locations with different latitudes and sky clearance factors. Results show that the effect of the sky clearance can overcome the effect of the latitude in terms of the effectiveness of solar tracking systems. The sky clearance factor suppresses the effect of the latitude as the sky clearance factor falls below 0.55.